2018
DOI: 10.1038/s41419-018-1003-1
|View full text |Cite
|
Sign up to set email alerts
|

Loperamide, pimozide, and STF-62247 trigger autophagy-dependent cell death in glioblastoma cells

Abstract: Autophagy is a well-described degradation mechanism that promotes cell survival upon nutrient starvation and other forms of cellular stresses. In addition, there is growing evidence showing that autophagy can exert a lethal function via autophagic cell death (ACD). As ACD has been implicated in apoptosis-resistant glioblastoma (GBM), there is a high medical need for identifying novel ACD-inducing drugs. Therefore, we screened a library containing 70 autophagy-inducing compounds to induce ATG5-dependent cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 80 publications
7
46
0
Order By: Relevance
“…Interestingly, in contrast to our findings that classify STF-62247 as an inducer of autophagic flux and ACD, STF-62247 has recently been reported to block late stages of autophagy by inducing lysosomal disruption in von Hippel-Lindau (VHL)-deficient renal cell carcinoma cells 80 . This study however emphasized that VHL-competent cells are capable to overcome this block of late stages of autophagy and to maintain high lysosome numbers, which is consistent with our data showing that STF-62247 enhances the autophagic flux of VHL-competent MEFs as well as GBM cell lines 30,80 . From a mechanistic perspective, this could be due to STF-62247-induced inhibition the master regulator of autophagy, mTORC1, which we demonstrated in our previous study in GBM cells 30,81 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, in contrast to our findings that classify STF-62247 as an inducer of autophagic flux and ACD, STF-62247 has recently been reported to block late stages of autophagy by inducing lysosomal disruption in von Hippel-Lindau (VHL)-deficient renal cell carcinoma cells 80 . This study however emphasized that VHL-competent cells are capable to overcome this block of late stages of autophagy and to maintain high lysosome numbers, which is consistent with our data showing that STF-62247 enhances the autophagic flux of VHL-competent MEFs as well as GBM cell lines 30,80 . From a mechanistic perspective, this could be due to STF-62247-induced inhibition the master regulator of autophagy, mTORC1, which we demonstrated in our previous study in GBM cells 30,81 .…”
Section: Discussionsupporting
confidence: 92%
“…We previously reported that STF-62247 and pimozide increase the autophagic flux of a panel of GBM cell lines 30 . To further evaluate the effects of STF-62247 and pimozide on autophagy induction in MEFs, we initially investigated some of the major hallmarks of autophagy 19,20 .…”
Section: Stf-62247 and Pimozide Trigger Autophagy In Mefsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent reports also highlighted that lysosomal homeostasis is essential in cancer stem cell survival 18,21 . Additionally, it has been shown that targeting the autophagic machinery is an effective treatment against apoptosis-resistant GBM 22,23 . The autophagic flux inhibitor chloroquine can decrease cell viability and acts as an adjuvant for TMZ treatment in GBM.…”
Section: Introductionmentioning
confidence: 99%